Justified use of 5% amorolfine nail lacquer, in the treatment of toe onychomycosis - Liubov P. Kotrekhova; Ekaterina N. Tsurupa; Galina A. Chilina; Ilia A. Bosak; Arina A. Vashkevich (State Scientific Center of Dermatovenereology and Cosmetology, 2023)
The article presents the description of three clinical cases of the successful treatment of toe onychomycosis and athlete's foot of various etiologies using 5% amorolfine antifungal nail lacquer. The first case: a 31-year-old woman was diagnosed with white superficial onychomycosis of great toe caused by Trichophyton rubrum. The treatment with 5% amorolfine once a week for 6 months resulted in full recovery (both mycological and clinical). The second case: a 42-year-old woman developed onychomycosis after the application of decorative coating on her nails; onychomycosis was caused by Scopulariopsis brevicaulis. She was treated with itraconazole pulse therapy and 5% amorolfine lacquer. She fully recovered. The third case: a 65-year-old man with total onychomycosis of 10 toes developed the skin mycosis of the left foot and lower third of the leg. He was prescribed a therapy with sertaconazole cream and 5% amorolfine lacquer. The use of 5% amorolfine lacquer was continued to prevent from recurrent dermatomycosis. Thus, the above mentioned cases are a good example of the advantages of using 5% amorolfine lacquer in the treatment of most toe onychomycosis types caused by any pathogens (dermatophytes, yeasts or molds).